2006
DOI: 10.1002/biof.5520270113
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the TPA‐induced inhibition of gap junctional intercellular communication by Chaga mushroom (Inonotus obliquus) extracts: Effects on MAP kinases

Abstract: Chaga mushroom (Inonotus obliquus) has continued to receive attention as a folk medicine with indications for the treatment of cancers and digestive diseases. The anticarcinogenic effect of Chaga mushroom extract was investigated using a model system of gap junctional intercellular communication (GJIC) in WB-F344 normal rat liver epithelial cells. The cells were pre-incubated with Chaga mushroom extracts (5, 10, 20 microg/ml) for 24 h and this was followed by co-treatment with Chaga mushroom extracts and TPA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…These results are in agreement with those of Markaverich et al (15) who showed that DBL also downregulates cyclin D1 and c-myc levels and that it finally leads inhibition of cell proliferation in estrogen receptorpositive and estrogen receptor -negative cells. Previous reports suggest that DBL inhibits proliferation of cells and induces apoptosis in various tumor cells (15,40). It is possible that these effects of DBL are mediated through the down-regulation of antiapoptotic gene products and cyclin D1 and c-myc as described here.…”
Section: Discussionmentioning
confidence: 50%
“…These results are in agreement with those of Markaverich et al (15) who showed that DBL also downregulates cyclin D1 and c-myc levels and that it finally leads inhibition of cell proliferation in estrogen receptorpositive and estrogen receptor -negative cells. Previous reports suggest that DBL inhibits proliferation of cells and induces apoptosis in various tumor cells (15,40). It is possible that these effects of DBL are mediated through the down-regulation of antiapoptotic gene products and cyclin D1 and c-myc as described here.…”
Section: Discussionmentioning
confidence: 50%
“…The Chaga mushroom, Inonotus obliquus, is a fungal parasite, which is claimed to have natural beneficial properties for human health such as anti-bacterial, anti-allergic, anti-inflammatory and antioxidant activities protecting cell components against free radicals [21]. In a model system for gap junctional intercellular communication (GJIC), its extract has been shown to prevent the inhibition of GJIC in WB-F344 normal rat liver epithelial cells through the inactivation of ERK1/2 and P38 MAP kinases [26]. From the sclerotia of the Chaga mushroom various lanostane-type triterpenoids like inotodiol can be isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Zhong et al 43 described an effect of growth inhibition of lung carcinoma cells by inotodiol triterpenoid. An anti-cancerogenic effect of I. obliquus tinctures was studied also by Burczyk et al, 44 Lee et al, 45 Youn et al, 46 Nomura et al, 47 Chung et al, 48 Nakajima et al, 49 and Park et al 50 In the cited works, a positive antitumor action of I. obliquus extracts was demonstrated in hepatoma, leukemia, colon, and cervical carcinomas. Nakajima et al 49 show that phenolic compounds of metanolic I. obliquus extract demonstrate a target toxicity against several lines of cancer cells and the absence of cytotoxic effects against normal cells.…”
Section: Direct Antitumor Activitymentioning
confidence: 85%